Changyanning regulates gut microbiota and metabolism to ameliorate intestinal injury induced by ETEC K88 - Guo, Pei; Wang, Zongke; Lv, Xiaojing; Wang, Xin; Yu, Jiaying; Tian, Xuelei; Shan, Hu; Qin, Zhihua (Frontiers in Microbiology, 2023)
Enterotoxigenic Escherichia coli (ETEC) is a common pathogen of swine colibacillosis, which can causing a variety of diseases initiate serious economic losses to the animal husbandry industry. The traditional Chinese medicine Changyanning (CYN) often used for diarrhea caused by the accumulation of damp heat in the gastrointestinal tract, has anti-bacterial, anti-inflammatory and anti-oxidation effects. This study investigated the therapeutic effects and the mechanism of action for the oral administration of CYN on ETEC K88 infected mice by determining intestinal morphology, inflammatory responses, intestinal microbiota as well as metabolites. CYN administration elevated ETEC K88-induced body weight loss, ameliorated duodenum, ilem, colon pathological injury, and reduced the increase of spleen index caused by ETEC. CYN also reduced the levels of pro-inflammatory cytokines (IL-6, TNE-α) in the serum. 16s rRNA gene sequencing results showed that CYN increased the abundance of beneficial bacteria Lactobacillus but decreased the abundance of pathogenic bacteria Escherichia in the feces of mice. Moreover, CYN participates in amino acid biosynthesis and metabolism in the process of serum metabolism to regulates ameliorate intestinal injury induced by ETEC K88. In conclusion, CYN regulates gut microbiota and metabolism to ameliorate intestinal injury induced by ETEC K88.